1984
DOI: 10.1016/0014-5793(84)80768-1
|View full text |Cite
|
Sign up to set email alerts
|

N‐terminal amino acid sequences of chloroform/methanol‐soluble proteins and albumins from endosperms of wheat, barley and related species

Abstract: The N-terminal amino acid sequences of two chloroform/methanol soluble globulins from barley and one form wheat are reported. They are homologous with N-terminal sequences previously reported for a-amylase and trypsin inhibitors from cereals and 2 S storage proteins from castor bean and rape. Three albumins were also purified from Aegilops squarrosa and Triticum monococcum. These had N-terminal amino acid sequences most closely related to the a-amylase and trypsin inhibitors. The relationships of this superfam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…2. tetrameric inhibitors, fully confirm that indeed the three proteins are members of the same protein family as the monomeric and dimeric a-amylase inhibitors, the trypsin inhibitors and the bifunctional inhibitors from cereals [2,3,11,34,35,37]. The sequences of subunits CM1, CM16, CM3 and CMd are closer to each other (47-86% identical residues) than to any of the other proteins in Fig.…”
Section: P G C P R Ti V Fojm Fo" F V Rl I |L V|t|p G| Y |C N L| T Plsupporting
confidence: 66%
See 2 more Smart Citations
“…2. tetrameric inhibitors, fully confirm that indeed the three proteins are members of the same protein family as the monomeric and dimeric a-amylase inhibitors, the trypsin inhibitors and the bifunctional inhibitors from cereals [2,3,11,34,35,37]. The sequences of subunits CM1, CM16, CM3 and CMd are closer to each other (47-86% identical residues) than to any of the other proteins in Fig.…”
Section: P G C P R Ti V Fojm Fo" F V Rl I |L V|t|p G| Y |C N L| T Plsupporting
confidence: 66%
“…Nucleotide sequences and deduced amino acid sequences of inserts in clones pCTl, pCT2, and pCT3, which respectively correspond to subunits CM3, CMl, and CM16 of the wheat tetrameric a-amylase inhibitor (indicated in parenthesis). Sequences identical to known N-terminal sequences of proteins CM3B [37] CMl and CMl 6 [2] are boxed. The AATAAA polyadenilation signáis are underlined.…”
Section: Chromosomal Locations Of Genesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus it appears that the 2s Kunitz-type proteins and the 7 s and 12s globulins constitute a wider family of related proteins which may have evolved from a common ancestral precursor either by a process of gene duplication or exon deletion to produce the genes found today. This protein family, however, is distinct from the seed protein superfainily [29] which is characterized by the conservation of the number and positions of the cysteine residues and includes 2s albumins of wheat and inhibitors of trypsin and a-amylase from cereals, and 2s proteins of castor bean and rapeseed. In summary, the primary structure of the major seed albumin of winged bean seed has shown that it is related to the 2s Kunitz-type seed inhibitors and that this family of 2s proteins is related to the storage globulins found in many seeds.…”
Section: Resultsmentioning
confidence: 99%
“…Current evidence suggests that the cereal proteins of this type may belong to at least six distinct families. For example the a-amylase inhibitors from wheat [2][3][4], and rye [5], proteinase inhibitors from rye [5], barley [6] and maize [7], and a hifunctional a-amylase/trypsin inhibitor from ragi [8] belong to a so-called superfamily [9] which also includes the cereal chloroform-methanol (CM) soluble proteins and certain 2 S storage proteins from dicotyledonous plants. Other bifunctional inhibitors from barley [10,11], wheat [12,13] Correspondence address: M. Richardson, Department of Botany, University of Durham, Science Laboratories, South Road, Durham DHI 3LE, England and rice [14] have sequence homology with the legume Kunitz inhibitor family, while proteinase inhibitors from barley [15,16] clearly belong to the potato inhibitor 1 family.…”
Section: Introductionmentioning
confidence: 99%